2021
DOI: 10.3389/fmicb.2021.626691
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Comparison Between Intestinal Contents and Mucosa in Mice With Repeated Stress-Related Diarrhea Provides Novel Insight

Abstract: Repeated stress-related diarrhea is a kind of functional bowel disorders (FBDs) that are mainly stemming from dysregulation of the microbiota–gut–brain axis mediated by a complex interplay of 5-hydroxytryptophan (5-HT). Intestinal content and intestinal mucosa microbiota belong to two different community systems, and the role of the two microbiota community systems in repeated stress-related diarrhea remains largely unknown. In order to ascertain the difference in composition and the potential function between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…Therefore, microorganisms in different intestinal areas are relatively different in their composition, function, and response to external substances. For example, the intestinal mucosal microbiota is more sensitive to repeated stress-related diarrhea than the intestinal content microbiota, and more sensitive to dietary factors than the fecal microbiota [ 42 , 54 ]. Furthermore, the body lactase could be derived from the villi of intestinal mucosal epithelial cells, and the integrity of the intestinal mucosal is an important guarantee for the lactase to play the function of digestion of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, microorganisms in different intestinal areas are relatively different in their composition, function, and response to external substances. For example, the intestinal mucosal microbiota is more sensitive to repeated stress-related diarrhea than the intestinal content microbiota, and more sensitive to dietary factors than the fecal microbiota [ 42 , 54 ]. Furthermore, the body lactase could be derived from the villi of intestinal mucosal epithelial cells, and the integrity of the intestinal mucosal is an important guarantee for the lactase to play the function of digestion of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota is composed of LAB and MAB with different ecological niches. LAB are mainly related to metabolism, whereas MAB are closely related to immunity (Zhang et al, 2021). To comprehensively analyze the effects of SIs on the gut microbiota, we observed changes in LAB and MAB after SIs treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with our PCoA and NMDS results, a high salt diet clearly changed the structure of the gut microbiota, and intestinal bacteria may show increased growth in hypertensive animals. In fact, many recent studies have reported that increased growth of gut bacteria is common in patients with a variety of diseases ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%